A study on the influence of rural tourism’s perceived destination restorative qualities on loyalty based on SOR model - Zhu, Ning; Xu, Haochen; Zhang, Xi; Chen, Li (Frontiers in Psychology, 2025)
IntroductionTourists’ restorative perception of the environment in rural tourism is a key factor to enhance tourism experience and promote physical and mental recovery, as well as a new perspective of tourist psychological research. However, the current research on the impact of tourists’ perceived destination restorative qualities on loyalty in rural tourism has not been deeply discussed.MethodsBased on the Stimulus-Organism-Response (SOR) framework, this study explores the relationship between tourists’ perceived destination restorative qualities, well-being (hedonic experience and eudaimonic experience), destination image and loyalty. Through a questionnaire survey, 489 valid questionnaires were obtained and analyzed by structural equation model.ResultsThe results show that: (1) Perceived destination restorative qualities have a direct positive impact on hedonic experience, eudaimonic experience and destination image; (2) Both hedonic experience and eudaimonic experience have a direct positive impact on destination image and loyalty, in which the impact of hedonic experience is greater; (3) The relationship between destination image and loyalty is not significant.DiscussionThe research results provide important guiding significance and enlightenment for the development of rural tourism.